The third option is the answer
Step-by-step explanation:
C=(3.14)(15)
you multiply and get 47.1
Answer:
Step-by-step explanation:
(3m-1)(6-a)-(m+3)(6-a)
=3m(6-a)-1(6-a)-m(6-a)+3(6-a)
=18m-3ma-6+a-6m+ma+18-3a
=12m-2ma+12-2a
=2(6m-ma+6-a)
<h3>
Answer: Choice A) <9,0></h3>
Explanation:
Focus on one of the points in the figure on the left. Let's say we go for the upper left corner point (-7, 4)
Notice it moves to the corresponding image point (2,4). It has shifted 9 units to the right to follow the translation rule
. We've added 9 to the x coordinate, and the y coordinate stays the same.
This notation can be shortened to <9, 0>
In general, the notation
is shortened to the translation vector notation
. In this case, a = 9 and b = 0.